Legal Drafting in the Ottoman Period - Meirison Meirison (Jurnal Ilmiah Al-Syir'ah, 2019)
Ottoman Turkey is a country based on Islamic Shari'a in which all cases that will decide must refer to Islamic shari'a. The door of Ijtihad has been closed for a long time, thus opening the opportunity for the authorities to issue legal decisions after being investigated by scholars. The design process is complicated because the books of fiqh do not instantly explain the laws required. The legal drafting process in principle based on the Qur'an and al-Hadith which are manifested by the mufti or Syaik al-Islam after being proposed by the sultan through the prime minister. After obtaining syaikh al-Islam's approval, the law or law is deemed legitimate. With a qualitative approach, the author conducted a literature study and analyzed the data collected and interpreted legal drafting during the Ottoman period. The decline of the Ottoman Empire in various fields has led to renewal including reforms in the areas of legislation, law, and justice which demanded legal codification in the form of majallah Al-Ahkam Al-Adliyah. This Majallah contains the law mu'amalah, which leads to ahwal As-syakhsiyah and serves to maintain Islamic law, which almost eliminated due to secularity that occurred.